Pengembangan Bahan Ajar Teks Eksplanasi Berbantuan Aplikasi Canva Pada Siswa Kelas VIII - Nanda Dwi Rifani; Rosmaini Rosmaini (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research aims to, (1) determine the process of developing teaching materials explanatory text assisted by the Canva application, (2) describes the shape development of explanatory text teaching materials assisted by the Canva application, (3) measuring the feasibility of developing assisted explanatory text teaching materials Canva application for class VIII students. This research uses samples as many as 30 students in class VIII-3 at SMP Al-Washliyah 30 Sukoharjo Medan with the research and development (R&D) method developed by Sugiyono 2017 with stages of potential and problems, data collection, design product, product validation, product revision, and product testing. Instruments that used inthis research is the Likert scale on the material validation questionnaire, media, teacher assessment, and student responses. The research results show that Explanatory text teaching materials assisted by the Canva application for class VIII SMP students including the "very good" criteria which can be seen from the validation of the material to obtain a score 94.25% in the "very good" category, media validation received a score of 95% with the "very good" category, and the teacher's assessment of the subject area received a score 97.5% in the "very good" category. Therefore it can be concluded that Explanatory text teaching materials assisted by the Canva application are suitable for use in the learning process.